UPAYA PENINGKATAN DETEKSI DINI KANKER PAYUDARA MELALUI EDUKASI BERBASIS PRAKTIK PADA IBU DASA WISMA DESA ARDIMULYO - Ermadona, Miftakhul Mahfirah; Mauludiyah, Indah; Hidayati, Ulfa Nur (Jurnal Abdi Masyarakat, 2024)
Breast cancer is one of the most prevalent types of cancer among women in Indonesia. Early detection through Breast Self-Examination (BSE) can increase the chances of successful treatment and reduce mortality rates. However, the knowledge and skills of women in performing BSE remain low, especially among community groups such as Dasa Wisma mothers, who play an essential role in the family and community environment. This community service program aims to improve the knowledge and skills of Dasa Wisma mothers regarding Breast Self-Examination (BSE) through a practice-based educational program in Ardimulyo. The method used was a participatory educational approach with a pretest-posttest design to measure changes in knowledge and skills. The results showed a significant increase in the knowledge (p < 0.05) and skills of Dasa Wisma mothers in performing BSE after the intervention. The average knowledge score increased by 40%, and skills increased by 50% compared to before the intervention. This practice-based educational program was effective in improving the knowledge and skills of Dasa Wisma mothers regarding BSE. The implementation of similar programs in various other community groups can be a strategic step in supporting early detection of breast cancer.